A Redox‐Active 2D Metal–Organic Framework for Efficient Lithium Storage with Extraordinary High Capacity - Jiang, Qiang; Xiong, Peixun; Liu, Jingjuan; Xie, Zhen; Wang, Qinchao; Yang, Xiao‐Qing; Hu, Enyuan; Cao, Yu; Sun, Jie; Xu, Yunhua; Chen, Long (Angewandte Chemie (International ed.), 2020)
Metal–organic framework cathodes usually exhibit low capacity and poor electrochemical performance for Li‐ion storage owing to intrinsic low conductivity and inferior redox activity. Now a redox‐active 2D copper–benzoquinoid (Cu‐THQ) MOF has been synthesized by a simple solvothermal method. The abundant porosity and intrinsic redox character endow the 2D Cu‐THQ MOF with promising electrochemical activity. Superior performance is achieved as a Li‐ion battery cathode with a high reversible capacity (387 mA h g−1), large specific energy density (775 Wh kg−1), and good cycling stability. The reaction mechanism is unveiled by comprehensive spectroscopic techniques: a three‐electron redox reaction per coordination unit and one‐electron redox reaction per copper ion mechanism is demonstrated. This elucidatory understanding sheds new light on future rational design of high‐performance MOF‐based cathode materials for efficient energy storage and conversion. A high‐performance MOF: A conductive and redox‐active copper–benzoquinoid 2D metal–organic framework (MOF) with high capacity was designed for Li‐ion batterie. A new Li‐ion storage mechanism was unveiled by comprehensive spectroscopic methods.